1981
DOI: 10.1136/oem.38.4.356
|View full text |Cite
|
Sign up to set email alerts
|

Occupational and individual factors in acute shoulder-neck disorders among industrial workers.

Abstract: Twenty workers, consecutively attending the industrial health care centre for the first time with acute shoulder-neck pains, were subject to extensive rheumatological and ergonomic examinations. In seven patients congenital malformations or diseases causing musculoskeletal symptoms, or both, were probable aetiological factors. In the remaining 13 patients a significantly higher load was found on both shoulders (assessed by biomechanical film analysis) than in matched controls. The aim of the present investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
3

Year Published

1988
1988
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 15 publications
0
60
0
3
Order By: Relevance
“…This population was of particular interest because of their increased risk for developing shoulder problems. 3,8,9 In addition, we believe that people who do not engage in overhead activities, even though they might not have symptoms of shoulder impingement, may demonstrate abnormal kinematic patterns that could contribute to the development of shoulder impingement if they routinely used their arms in elevated positions. We believed that equal occupational exposure between the 2 groups would improve the potential to detect kinematic or muscle activity differences.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…This population was of particular interest because of their increased risk for developing shoulder problems. 3,8,9 In addition, we believe that people who do not engage in overhead activities, even though they might not have symptoms of shoulder impingement, may demonstrate abnormal kinematic patterns that could contribute to the development of shoulder impingement if they routinely used their arms in elevated positions. We believed that equal occupational exposure between the 2 groups would improve the potential to detect kinematic or muscle activity differences.…”
Section: Subjectsmentioning
confidence: 99%
“…Frequent or sustained shoulder elevation at or above 60 degrees in any plane during occupational tasks has been identified as a risk factor for the development of shoulder tendinitis or nonspecific shoulder pain. 3,8,9 Evidence relating occupational exposure of frequent or sustained shoulder elevation to shoulder musculoskeletal symptoms is strongest for combined exposure to multiple physical factors, such as holding a tool while working overhead. 9 Multiple theories exist as to the primary etiology of shoulder impingement, including anatomic abnormalities of the coracoacromial arch or humeral head 10,11 ; "tension overload," ischemia, or degeneration of the rotator cuff tendons [12][13][14] ; and shoulder kinematic abnormalities.…”
mentioning
confidence: 99%
“…Also other symptoms seem to be more common among workers in repetitive jobs. A particularly high risk of neck and shoulder pain also seems to be present in repetitive work (LuopajErvi et al 1979, Bjelle et al 1981, Kvarnstr6m 1983. It must be observed that continuous and repetitive arm movements give rise to static muscle load in the shoulder muscles.…”
Section: Repetitive Workmentioning
confidence: 99%
“…Using electromyographic fatigue indicators several authors have shown more rapid development of fatigue in the descending part of the trapezius muscle in patients with UEMDs compared to healthy subjects [40,45,129]. Bjelle et al [9,10] compared cases with acute, non-traumatic shoulder-neck pain to age-and sex-matched, paired controls. An increased blood concentration of creatine kinase (CK), a marker of muscle damage, was found in a substantial part of the cases.…”
Section: Clinical Findings: Signs and Symptomsmentioning
confidence: 99%